Fabry Disease: prevalence of affected males and heterozygotes with pathogenic GLA mutations identified by screening renal, cardiac and stroke clinics, 1995–2017. Issue 4 (12th January 2018) - Doheny, Dana; Srinivasan, Ram; Pagant, Silvere; Chen, Brenden; Yasuda, Makiko; Desnick, Robert J
Abstract : Background: Fabry Disease (FD), an X linked lysosomal storage disease due to pathogenic α-galactosidase A ( GLA ) mutations, results in two major subtypes, the early-onset Type 1 'Classic' and the Type 2 'Later-Onset' phenotypes. To identify previously unrecognised patients, investigators screened cardiac, renal and stroke clinics by enzyme assays. However, some screening studies did not perform confirmatory GLA mutation analyses, and many included recently recognised 'benign/likely-benign' variants, thereby inflating prevalence estimates. Methods: Online databases were searched for all FD screening studies in high-risk clinics (1995–2017). Studies reporting GLA mutations were re-analysed for pathogenic mutations, sex and phenotype. Phenotype-specific and sex-specific prevalence rates were determined. Results: Of 67 studies, 63 that screened 51363patients (33943M and 17420F) and provided GLA mutations were reanalysed for disease-causing mutations. Of reported GLA mutations, benign variants occurred in 47.9% of males and 74.1% of females. The following were the revised prevalence estimates: among 36820 (23954M and 12866F) haemodialysis screenees, 0.21% males and 0.15% females; among 3074 (2031M and 1043F) renal transplant screenees, 0.25% males and no females; among 5491 (4054M and 1437F) cardiac screenees, 0.94% males and 0.90% females; and among 5978 (3904M and 2074F) stroke screenees, 0.13% males and 0.14% females. Among male and female screenees with pathogenic mutations, the type 1 Classic phenotype was predominant ( 60%), except more male cardiac patients (75%) had type 2 Later-Onset phenotype. Conclusions: Compared with previous findings, reanalysis of 63 studies increased the screenee numbers ( 3.4-fold), eliminated 20 benign/likely benign variants, and provided more accurate sex-specific and phenotype-specific prevalence estimates, ranging from 0.13% of stroke to 0.9% of cardiac male or female screenees.